Natural Cubic Spline Method as a Method in Constructing a Life Table in Gegelang Village West Lombok - Fauzi, Andri Azmul; Ridwan, Lalu Muhammad; Agustini, Dwi; Putri, Desi Febriani; Tumilaar, Rinancy; Asmaidi, Asmaidi; Raming, Indriasri (Eigen Mathematics Journal, 2024)
This research aims to reconstruct a life table based on real data obtained in Gegelang Village, West Lombok. The data used in this research is the population in 2016, the death rate in 2014-2018 and the birth rate in 2014-2018. The first step taken was to compile a rough life table using the partial data situation and full data situation methods. Both methods are included in the maximum likelihood method. After carrying out calculations, different life expectancy figures are obtained. The respective calculation results were 62.21 years for the partial data situation method and 73.07 years for the full data situation method. Next, a graduation is carried out using the natural cubic spline method on the life table obtained from a rough life table model calculation. The graphic model produced by the rough life table is fluctuating so it is necessary to graduate using the natural cubic spline method to obtain a monotonically decreasing graph. The life table model chosen for graduation is a life table whose life expectancy is close to the life expectancy of West Lombok Regency in 2015, namely 65.1 years. After graduation, the new life expectancy was found to be 66.92 years.